Processo de design de serious game sobre prevenção de quedas em pessoas idosas hospitalizadas: definição de conteúdo - Veras, Rafaella Felix Serafim (2020)
Introduction: Hospitalized elderly people are at high risk of falls due to the synergistic action of intrinsic and extrinsic elements. The development of educational strategies to prevent falls associated with technological resources with specific pedagogical purposes, such as serious games, can benefit these individuals in preserving their safety while they are hospitalized. Objective: To determine the specific content of a serious game about preventing falls in hospitalized elderly people. Method: A methodological study carried out in three stages was developed: an integrative literature review on risk factors for falls in hospitalized people; workshops with nurses, patients and companions on preventing falls in hospitalized people; determination of the specific content of the serious game on preventing falls in hospitalized elderly people. The interpretation of the data in the first and second stage of the work took place automatically using the PorOnto tool, which allowed the identification, selection and categorization of terms related to the theme with their respective frequency of occurrence in the analyzed texts. The results of the integrative literature review were displayed in charts and flowcharts and the data from the workshops and the specific content of the serious game were presented through Concept Maps containing the key elements for the occurrence of falls in hospitalized people. The study was approved by the Research Ethics Committee under opinion 2,958,750 and CAAE: 99957018.4.0000.5183. Results: The identification of risk factors for falls in hospitalized people was carried out from 36 publications, which presented 2248 terms related to intrinsic risk factors and 512 that related to extrinsic risk factors. The workshops took place with the participation of 15 nurses, 09 patients and 11 companions with a selection of 199 terms in the workshops with nurses, 56 in the workshop with patients and 81 in the workshop with companions. These were categorized into intrinsic and extrinsic key elements. Therefore, by combining the elements identified in the publications and workshops, the specific content of the serious game on fall prevention was defined. This included the awareness of hospitalized people about the risks of falls considering key elements that trigger falls distributed patient limitations and characteristics of the environment. The patient's limitations are related to the following key elements: knowledge about falls, physiological and behavioral. Regarding the characteristics of the environment, subcategories were identified regarding infrastructure, equipment configuration and hospital routine. Conclusion: The shared construction of the specific content of the serious game has the potential to subsidize health education for the prevention of falls by presenting a specific approach on the theme based on the reality of those involved in the care and prevention of accidents in hospitalized elderly people.